Mediação da Comissão Pastoral da Terra nos conflitos agrários do oeste paranaense (1964-1985) - Souza, Hiolly Batista Januário de (2017)
This dissertation studied the mediating work carried out by the Land Pastoral Commission (CPT) in agrarian conflicts in the western region of Paraná, resulting from the construction of the Itaipu Binational Hydroelectric Power Plant and its lake; the process of modernization of agriculture, etc. The chronological cut for the aforementioned study began in 1964, extending to 1987. Presenting the historical contextualization of Brazil and the region in the first chapter; discussing Liberation Theology and its influence on pastoral work within the "preferential option for the poor", as well as the relations between the Catholic Church and the Brazilian dictatorial government. The first chapter refers to the Brazilian politico-social contextualization in the 1960s and 1970s; of the occupation process of the western region, the mechanization of agriculture. We continue with the second chapter that seeks a discussion on the progressive wing of the Catholic Church and the influence it had on CPT's actions in western Paraná. The third chapter deals exclusively with the Commission's actions with rural workers, participating in its organization and its struggles. Analyzing the constitution of organizations such as the Justice and Land Movement (MTJ) and the Landless Farmers Movement of the West of Paraná (MASTRO), and other CPT work fronts as opposed to the colonization projects, immigration to the central regions -west and north, conflicts between settlers and indigenous people.